COMPOSITION, STRUCTURE AND PHYSICAL - CHEMICAL PROPERTIES OF PHOSPHOGYPSUM - Jovliyev Ziyodulla (Galaxy International Interdisciplinary Research Journal, 2022)
Phosphogypsum is a grayish powdery mass of various moisture content collected in piles. In the process of processing Karatau phosphorites, it is formed from the conversion to phosphoric acid in the production of phosphorus fertilizers. According to information, the total amount of phosphogypsum accumulated in Uzbekistan is approximately 80 million. tons, of which 45 million in Almalyk chemical plant, 25 million in Samarkand chemical plant, 10 million in Yangikokan chemical plant. is a ton. Currently, the Yangikokan chemical plant is closed. 2,570,000 tons of phosphogypsum in the amount of 1,580,000 tons at the Samarkand chemical plant are dumped into heaps every year. The average chemical composition of phosphogypsum, in %, is as follows: CaO 26; SO3 36; SiO2 15; Al2O3 0.3; Fe2O3 0.2; MgO 0.01; P2 O5 1.2; fluorides 0.1-0.4.